Analysis Corelation Between Work Demands With Stress Labor at Laboratory X Kediri City: Analisis Hubungan Tuntutan Kerja Dengan Perubahan Stres Tenaga Kerja Pada Laboratorium X di Kediri - Sumaningrum, Ningsih Dewi (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
Potential psychosocial hazards are potential hazards caused by the psychological aspects of labor that are not good enough and are not getting enough attention including unsuitable placement of workers, unharmonious and incompatible relationship among individuals in the work organization, work demands, and stress. Excessive work demands not according to ability, target time, concurrent work can cause stress labor. Stress can have bad effect on the safety and health workers. Work stress is a person’s reaction to excessive presure or demands at work detrimental. Purpose This study aims to analyze the correlation between work demands and psychological changes especially stress at laboratory Kediri city. This study design was a quantitative study with a cross sectional approach. Data collection was carried out using quick test questionnaire to detect work stress standardized by the ministry of health. Sampling this study was conducted with a total sampling technique of 14 respondents. The statistical test used was the pearson correlation test. Pearson correlation test results obtained a significance value of 0.046. Thus this value is smaller than 0.05 so it can be concluded that there is significant which means there was a correlation work demands with psychological changes in this case work stress. The company should perform management of work demands, so that the workforce can work comfortably, work productively, and be free from work stress.